AGRIBUSINESS MARKET DEVELOPMENT CASE STUDY : RUBBER - Taufik Hidayat (UPT Penerbitan Universitas Jember, 2012)
The Economic crisis faced by Indonesia since 1998 caused three fundamentalproblems : (1) The Crisis made Indonesia's economy had contraction around -13.2% in1998; (2) The amount of unemployment continued rising; (3) The crisis made thedistribution aspect and income distribution worse. The plantation development is one ofthe options is quite realistic with the three main reasons: (1) The plantation business has ahigh resistance; (2) The plantation business is still highly prospective; (3) The plantationbusiness is expected to absorb more labors, while improving income distribution.Rubber is one of the essential commodities due to it is: sources of revenue,employment availability; foreign exchange; driver of economic growth in the new centersaround the rubber plantations; and protecting the environment. The current condition inrubber agribusiness indicates that the rubber is managed by: people, (85%), country estatesand private estates. The obstacles of people plantation are: low productivity, the quality ofrubber is not in accordance with ISO Standard, there is no source of funds for replanting,the replanting is still slow, the domestic consumption is 7% of the total production, there isno marketing & promotion media. Problems of marketing and promotion are many areasdo not have marketing and promotion centers, limited information, the role of thegovernment is low, speculators still have dominant role.The following steps are necessary to be done as solutions: direct marketing(shortening the chain of trade by bringing the buyers to the rubber farmers); third-partymarketing (co-marketing arrangements with other companies); establishing centers for thesale or marketing; the role of government (creating and empowering the rubber auctionmarket). Efforts to increase productivity and income from rubber can be done through:establishment of promotion and marketing institution in the people's plantations,establishment of the auction institution, establishment of the rubber Cooperative agency forfarmers, acceleration of plantation rejuvenation via credit with low interest rates, the use ofsuperior rubber planting materials, plantation diversification and planting patterns,infrastructure and production development , processing of rubber and rubber goods industries as well , ease of regulatory and legal certainty which are the incentives forinvestors.